2007
DOI: 10.2298/bah0702139r
|View full text |Cite
|
Sign up to set email alerts
|

The characteristic of control day milk and its properties in ewes from different breeds in Bulgaria

Abstract: Abstract:The aim was the investigation the milk and its composition for control day in local sheep breeds. The experiment was carried out with 19 Karakachan ewes and 21 West Balkan Mountain ewes from the flock of IAS-Kostinbrod and 15 Local Sofia ewes from a private flock from village Klisura. The study is a part of Bulgarian-Greece project for research of F1-crosses of Chios breed. The experimental ewes were mothers of F1 Chios' crosses. The milk for day was recorded on first control during milking period. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…The values of milk fat in the present study were close to those previously reported by other authors (5.91 -7.82%) [4,5,8,12,14]. Correlation models for lactose content and density in raw sheep's milk have been developed.…”
Section: Fig 4 Linear Correlation Between Dry Matter and Milk Fatsupporting
confidence: 91%
See 2 more Smart Citations
“…The values of milk fat in the present study were close to those previously reported by other authors (5.91 -7.82%) [4,5,8,12,14]. Correlation models for lactose content and density in raw sheep's milk have been developed.…”
Section: Fig 4 Linear Correlation Between Dry Matter and Milk Fatsupporting
confidence: 91%
“…The highest fat-free residue values for the period were reported in April (beginning of the milking campaign) -12.76%. It was higher (10 -11.45%) than previously reported [12][13][14] obtained by sheep considered as cross between a Karakachan sheep and a Pleven black-headed ram. At the end of the lactation period, the values of the dry non-fat residue had decreased to 11.85%, which is close to the previously reported mean values for milk from the Karakachan sheep breed [5].…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation